Pengaruh Bimbingan Konseling Kelompok Dengan Teknik Assertive Training Untuk Peningkatan Keterampilan Sosial Siswa Di Smp Negeri 6 Pangkalpinang - zaman, iffah nur zaman; Bohhori (Department of Islamic Guidance and Counseling, 2025)
Social skills are a crucial aspect of development, especially for students as they begin to develop their identity and personality. The study focused on students at SMP Negeri 6 Pangkalpinang because some of them experienced social skills problems. Therefore, group counseling using the Assertive Training technique was implemented to improve social skills. The research method used a quantitative approach with a one-group pretest–posttest design. The results showed a significant difference between the pre-test and post-test scores of students' social skills after being given Assertive Training. The results showed that 97.7% of the increase in students' social skills was directly influenced by the Assertive Training intervention. Based on these findings, this study concludes that Assertive Training is effective in improving students' social skills. The practical implication of this research is that the Assertive Training technique can be used as a group counseling intervention strategy by guidance counselors to help students develop more adaptive, confident, and constructive social skills.